CLIMATE-REGULATING FUNCTIONS OF OAK STANDS OF THE VELIKOANADOLSKY FOREST AREA - Tkach, V. P.; Kobets, O. V.; Rumiantsev, M. G. (Forestry and Forest Melioration, 2018)
Introduction Forests create a special microclimate both in the stands and on the surrounding areas. As we move towards the south, forests reduce high air temperatures, change the radiation and temperature conditions and increase air humidity. Biomass of plants, including its ground and underground parts, are the main absorber of carbon dioxide from the atmosphere. About half of the carbon dioxide absorbed by plants is taken by them for breath and returned to the atmosphere. The rest of the carbon dioxide forms a total production of biomass. The oak has the ability to sequester significant amounts of carbon and form the biomass due to structural features of leaf and crown. There is still no information on the volume of carbon fixation in oak stands of the northern steppe, in particular, in stands of the Velikoanadolsky forest area which perform important ecological and protective functions. The aim of the study is a quantitative assessment of environmental functions of oak stands in the Velikoanadolsky forest area. Materials and Methods Analysis and assessment of climate-regulating functions of oak stands of the Velikoanadolsky forest area were made based on long-term (1895–2016) temperature and precipitation observations obtained by the meteorological station of the State Enterprise «Mariupol Forest Research Station» and by Volnovaha and Rozovka weather stations. To determine the phytomass, regulatory tabular data and developed yield tables for modal oak stands of the Velikoanadolsky forest area were used. Results The area of the Velikoanadolsky forest area relates to dry and relatively warm climate forest typological district of Donetsk ravine forests. The studied period (1895–2016) is distinguished by intensification of continentality from the 1990’s and saturation deficit. That causes worsening of natural and climatic conditions for the forests of this region. Against the increase in the average annual atmospheric precipitations up to 500 mm (600 mm and more in particular years), there is their redistribution over autumn and winter season. The dynamics of biological productivity of oak stands by the aboveground and the total phytomass was calculated using the II site class modal stands in fresh elm-maple oak forest site. According to the calculations, one hectare of 50-year-old oak plantation accumulates over 66 tons of carbon and more than 93 tons, when combined with the part what is eliminating from the stands. One hectare of 100-year-old oak plantation accumulates 132 and 295 tons of carbon, respectively. Artificial oak plantations of the forest area accumulate over 250 thousand tons of carbon. The high level of current increment of oak stand biomass is noted up to 70–90 years of age. Aging of stands of the forest area adversely affects the annual amounts of carbon deposition. The positive impact of the forest stands on the climate of the area is evident in reducing air temperature as well as preventing the negative effects of climate change. The territory of the Velikoanadolsky forest area is distinguished by lower amounts of positive monthly temperatures (108–111°C) compared to open space (113–120°C). The difference in the annual precipitation compared to open space has decreased from 7 to 4 % (480–500 mm vs. 445–480 mm) as a result of a drought period in the region and worsening of a health condition of the forests in the area over the last 15 years. However, the share of precipitations during the period of vigorous growth of plants in the forest area is larger (34–35 % vs. 28–33 %). The beneficial impact of the forest plantations on the climate of the area affects the indicators of climate humidity even against the drought period in the region. During 1990–2016, the difference between Selyaninov’s hydrothermal coefficients in the Velikoanadolsky forest area and in the open space gradually increases. As of 1992, it was 3 % (0.88 vs. 0.85), and in 2016 it amounted to 14 % (0.87 vs. 0.75). During the period from 1990 to 2016, the long-term annual average Vorobyov’s climate humidity index was +0.2…+0.3 in the territory of the Velikoanadolsky forest area and -0.1...-0.5 in the open area. The difference between the humidity indices during this period has increased from 0.4 to 0.7. A density, composition and storeyed structure of the stand also affect the changes of the area microclimate. The multi-storeyed mixed dense stands with significant undergrowth have a much larger impact on the climate of the area compared to the single-storeyed and pure stands. Conclusions Forest stands of Velikoanadolsky forest area perform important climate-regulating functions. The positive impact of the forest stands on the climate of the area is evident in reducing air temperature and preventing the negative effects of climate change. To improve the climate-regulating and carbon sequestering efficiency of the forest stands of the area, more resilient and long-lived multi-storeyed mixed dense stands with significant undergrowth should be created.